(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Any members of the human gut micro biota including members of the gut micro biota that promote health like bifid bacterium bifidbacterium spp. Catabolize manna’s for food. Few informationis available in the gut ecological niche regarding the enzymology of man nan deconstruction, below the biochemical properties if the first 5 subfamily 8 glycoside hydrolase (GH5 8) manna n as e derived from the biochemical properties of probiotic. The relationship between gut micro biota and biochemical metabolism to explore the relationship between gut micro biota. In traycomponents and some substances which are produced by the host, the primary intestinal microbe :bacteria and microbial species associated with dietary carbohydrates metabolism, strictly anaerobic and gram positive strain of specified bifid bacteria known as, B. Lon gum (60 percent of the sample )was the most commonly identified species followed by B. bifida (60 percent of the samples ), while B. Brief (21 percent).